Depressive symptoms during childhood and cardiovascular risk factors in black and white men - Matthews, Karen A. (Psychosom Med, 2019)
OBJECTIVE: Depressive symptoms and major depression predict cardiovascular disease (CVD) and CVD risk factors in adulthood. Evidence regarding the role of depression in the development of CVD risk in youth is minimal. The study evaluated the prospective relationship of depressive symptoms in childhood and adolescence with adult CVD risk factors in black and white men. METHODS: Health behaviors and medical history were measured in 165 black and 146 white men (mean age = 32); a subset in the Pittsburgh area had a fasting blood draw to measure metabolic syndrome and inflammation. Adult CVD risk factors were related to depressive symptoms and childhood socioeconomic status (SES) prospectively measured annually from ages 7 to 16 years, followed by adjustments for adult SES and depressive symptoms. RESULTS: Men with higher depressive symptoms ages 7 to 16 smoked more cigarettes, B = 0.28 (standard error, 0.12), p = .015, and ate fewer servings of fruits and vegetables, B = −0.08 (0.04), p = .040, as adults. The association for smoking was independent of adult depressive symptoms (concurrent) and childhood and adult SES as well as race. Depressive symptoms during childhood were unrelated to the metabolic syndrome or biomarkers of inflammation in adulthood. CONCLUSIONS: Depressive symptoms in childhood may predict later adverse health behaviors in black and white men. No evidence was found for an association between childhood depressive symptoms with metabolic syndrome or inflammation markers at ages around 32 years. The nature of the sample and lack of measurement of depressive disorder diagnosis tempers the conclusions, and future research is needed to determine associations with biological measures at later life span phases.